Factors Affecting the Performance of Indonesian Government´s Internal Supervisory - METALIA, MEGA; ZARKASYI, SRIHADI WINARNINGSIH; SUGARMAN, HARRY (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The role of the Indonesian government’s internal oversight apparatus (APIP) in guiding and supervising government institutions obliges them to maintain and improve its performance. This paper investigates the effect of management support, competence, objectivity, and integrity on the performance of the government’s internal oversight apparatus. The tool used in this data processing is SPSS. The results show that support for management, objectivity and integrity have a significant effect on APIP performance, while competition has a non-significant effect on APIP performance. Governments should be involved in supporting APIP performance by creating policies that can improve the management of internal oversight officers. RESUMEN El papel del aparato de supervisión interna del gobierno indonesio (APIP) en la orientación e inspección de las instituciones gubernamentales los obliga a mantener y mejorar su desempeño. Este trabajo investiga el efecto del apoyo a la gestión, la competencia, la objetividad y la integridad en el desenvolvimiento del aparato de supervisión interna del gobierno. La herramienta utilizada en este procesamiento de datos es SPSS. Los resultados muestran que el apoyo a la gestión, la objetividad y la integridad tienen un efecto significativo en el desempeño de APIP, mientras que la competencia tiene un efecto no significativo en el desempeño de APIP. Los gobiernos deben participar en el apoyo al desempeño de APIP mediante la creación de políticas que puedan mejorar la gestión de los oficiales de supervisión interna.